1992
DOI: 10.1177/0887302x9201100111
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Size Information on Men's Prewashed Jeans

Abstract: Consumers use size statements on garment labels to locate garments with a satisfactory fit. Accurate size information assists consumers to make efficient decisions in finding specific garments to purchase or to try on. The purpose of this study was to determine the accuracy of information on garment size labels. Two hundred and forty men'sprewashed jeans were measured to identify discrepancies between the stated and measured dimensions of the waist and inseam. The paired t-test and analysis of variance were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Manufacturers of more expensive clothing reportedly tend to increase the physical dimensions to satisfy customers who want to believe that they fit a smaller size. There is evidence to support these claims; Kiley (2005) Sieben and Chen-Yu (1992) …”
Section: Methodsmentioning
confidence: 90%
“…Manufacturers of more expensive clothing reportedly tend to increase the physical dimensions to satisfy customers who want to believe that they fit a smaller size. There is evidence to support these claims; Kiley (2005) Sieben and Chen-Yu (1992) …”
Section: Methodsmentioning
confidence: 90%
“…In the literature, Sieben and Chen-Yu (1992) reported an accept- able tolerance level of 0.5 inch to 1 inch for men's jeans offered for retail sale, depending on the seam and the manufacturer. Six sizes were measured (4, 6, 8, 10, 12, and 14).…”
Section: Methodsmentioning
confidence: 99%
“…That is, a size 6 in an expensive brand will be larger in dimension than a size 6 in an inexpensive brand, as an attempt to appeal to the vanity of customers who want to think of themselves as wearing a smaller size (Brown & Rice, 1998). Sieben and Chen-Yu (1992) found that an inverse price to size relationship existed for men's jeans. An image consultant and personal shopper reported that more expensive divisions of a designer's line (such as Anne Klein) would be sized a little larger than the less expensive line (Anne Klein II).…”
Section: Garment Size Dimensions and Pricementioning
confidence: 99%
See 1 more Smart Citation
“…Salusso-Deonier in Sieben and Chen-Yu (1992) states that consumers often use garment fit as a means of evaluating the quality of the garment. Brown and Rice (1998:39) agree with this view and state that fit affects comfort, as well as wear life of a garment.…”
Section: Introductionmentioning
confidence: 99%